PERBEDAAN AQ (ADVERSITY QUOTIENT) REMAJA DITINJAU DARI KELUARGA UTUH DENGANKELUARGA TIDAK UTUH - Faiko S.Psi.; Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan)
Adversity Quotient (AQ) is about how your respond to life, especially through the tough times. Adolescence is a transition phase of individuals from childhood to adulthood. Adolescents are challenged by many things in life, from everyday hassles to the big adversities of life. Family support often play major role for adolescent as model, as well as genetically transferred such traits to be able to confront their life issues. Sometimes family doesn’t provide the support needed by adolescent.The purpose of this study was to examine the AQ differences of adolescents from a whole family and adolescents from broken family. The population in this study are students of SMPN 1 Lekok, Pasuruan. The sample used are 60 students, taken by random sampling technique. Data collection using AQ scalewith validity coefficient between 0.312 – 0.597 and reliability coefficient equal to 0.644379. Identitiy form are used to seek students’ family background. The results of this research using intergroup t-tes shows thit is -0.10494 smaller than ttab 5% is 2.000, thus non-significant. There is no difference in AQ of adolescents from whole family and adolescents from broken family.